The Effectiveness of Compassion-Focused Therapy and Acceptance and Commitment Therapy on Post-Divorce Adjustment in Divorced Women Referred to Counseling Center in Ahvaz - Mahtab Ardeshirzadeh; Saeed Bakhtiarpour; Rezvan Homaei; Zahra Eftekhar Saadi (Shiraz University of Medical Sciences, 2022)
Background: Divorce, as an issue, can contribute to the development of a wide range of problems and consequences and frequently lead to an increased risk of social problems at both individual and social levels. The present study aimed to investigate the effectiveness of compassion-focused therapy (CFT) and acceptance and commitment therapy (ACT) on post-divorce adjustment in divorced women referred to the counseling center in Ahvaz city in 2019. Methods: The research method was quasi-experimental with a pre-test, posttest, and follow-up design and a control group. Using convenience sampling, we selected 45 divorced women willing to participate in the study. Then, we randomly divided them into two experimental groups (compassion-focused therapy and acceptance and commitment therapy) and a control group (n = 15 per group). The research instrument included the Fisher Divorce Adjustment Scale (FDAS). The first intervention program consisted of eight 60-minute sessions of compassion-focused therapy and the second intervention program consisted of ten 90-minute sessions of acceptance and commitment therapy. Results: The results showed that both compassion-focused therapy (CFT) and acceptance and commitment therapy (ACT) were effective in increasing post-divorce adjustment in divorced women (p<0.01). There was no significant difference between the CFT and ACT on post-divorce adjustment in this group of women (p>0.05). These results continued until the follow-up stage. Conclusion: According to research findings, both CFT and ACT were efficient therapies in increasing post-divorce adjustment in divorced women. Thus, both approaches can strengthen treatment interventions to increase adjustment in divorced women